Analysis of Overall Equipment Effectiveness (OEE) Enhancement With Total Productive Maintenance Improvements in Rubber Company - ALDA, TANIA; Bastanta Silalahi, Hiskia; Sinulingga, Sukaria (DINAMIS, 2024)
This research was conducted at a company engaged in rubber processing. This company plants, maintains, and processes rubber to produce Crumb Rubber. Based on observations during the study, it is known that there are defective products with an average of 400 kg per month. The type of defect found in the product is a white spot. Defects in these products are caused by failures in the performance of machines that experience thirst or collection, causing white spots in the products produced. This study aims to improve the company's performance by reducing defective products by analyzing the factors that cause a decrease in company performance, measuring the overall equipment effectiveness (OEE) value, and providing an improvement design to improve machine performance so that defective products can be minimized. The research found that two dominant factors cause high machine breakdowns: maintenance schedules and raw material quality. Based on the calculation results, the average overall equipment effectiveness value is 46%. Machine performance is not according to OEE standards due to the average value of the availability rate being 80%, the performance rate being 93%, and the quality rate being 57%. Based on this, the improvement design for the low OEE value is to improve the suggestion system, improve the quality control group, and implement the company's PDCA (Plan, Do, Check, Act) cycle.